2014
DOI: 10.1073/pnas.1422923112
|View full text |Cite
|
Sign up to set email alerts
|

Controlled analysis of nanoparticle charge on mucosal and systemic antibody responses following pulmonary immunization

Abstract: Pulmonary immunization enhances local humoral and cell-mediated mucosal protection, which are critical for vaccination against lung-specific pathogens such as influenza or tuberculosis. A variety of nanoparticle (NP) formulations have been tested preclinically for pulmonary vaccine development, yet the role of NP surface charge on downstream immune responses remains poorly understood. We used the Particle Replication in Non-Wetting Templates (PRINT) process to synthesize hydrogel NPs that varied only in surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 33 publications
3
111
0
Order By: Relevance
“…For instance, relative to anionic particles, cationic NPs appear to be taken up more readily via clathrin-mediated processes [21]. Furthermore, positively charged antigen-loaded NPs are significantly more effective at stimulating Th1 responses after either intradermal or mucosal (pulmonary) inoculation, whereas anionic particles stimulate T and B cell responses poorly under similar conditions [22,23]. The ability of cationic particles to stimulate Th1 responses has been associated with preferential DC uptake of such particles and the propensity of cationic particles to regulate positive costimulatory molecules [24].…”
Section: Chargementioning
confidence: 99%
“…For instance, relative to anionic particles, cationic NPs appear to be taken up more readily via clathrin-mediated processes [21]. Furthermore, positively charged antigen-loaded NPs are significantly more effective at stimulating Th1 responses after either intradermal or mucosal (pulmonary) inoculation, whereas anionic particles stimulate T and B cell responses poorly under similar conditions [22,23]. The ability of cationic particles to stimulate Th1 responses has been associated with preferential DC uptake of such particles and the propensity of cationic particles to regulate positive costimulatory molecules [24].…”
Section: Chargementioning
confidence: 99%
“…These formulations follow design principles of pathogen mimicry, as the majority of both bacteria and viruses have surfaces with acidic isoelectric points (26, 27). However, recent work from our group has demonstrated that pulmonary vaccination with cationic NPs can enhance local and systemic antibody production to a model antigen, as compared to otherwise equivalent anionic NPs (8). While these results indicate that nanoparticle charge is a key variable to immune responses in the lung, the underlying cellular mechanisms responsible for this deviation in immune response remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The next generation of vaccines can be achieved by pulmonary delivery of precision-engineered particles (1-8). Engineered micro- and nanoparticles (NP) offer elegant solutions for pathogen mimicry, while providing increased safety and efficacy over current vaccine strategies (2, 3, 6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a way to passively target DCs is through the reduction of the nanocarriers’ size. On the other hand, it is also known that providing nanocarriers with a positive surface charge enhances the chances for them to interact with DCs and macrophages [75,79,101103]. Nevertheless, irrespective of the influence of size and surface charge in the specific uptake of particles by dendritic cells, it seems clear that the most effective approach to precisely target DCs would be providing the nanocarriers with specific targeting ligands (Table 2B) [104].…”
Section: Access Of Nanostructures To Target Cellsmentioning
confidence: 99%